Evaluating various radiographic methods of shoulder joint damage in patients with rheumatoid arthritis receiving biological disease-modifying antirheumatic drugs - Kazuhito Sugimori; Isao Matsushita; Tomoatsu Kimura (Archives of Rheumatology, 2021)
Objectives: This study aims to clarify shoulder joint damage in rheumatoid arthritis patients receiving biological disease-modifying antirheumatic drugs (bDMARDs) and the relationship between joint damage and clinical factors. Patients and methods: In this retrospective study conducted between April 2005 and December 2008, 36 shoulders in 19 patients (2 males, 17 females; mean age: 58.9 years; range 42 to 75 years) were evaluated at baseline and two years after the initiation of bDMARD therapy with infliximab (n=14) or etanercept (n=5). Standard anteroposterior radiographs of the shoulder joints were taken at baseline and two years after institution of biological therapy. Structural damage in the shoulder joints was assessed using the Larsen scoring method, the medial displacement index (MDI), and the upward migration index (UMI). Results: There was a significant correlation between MDI, UMI, and Larsen grade before biological therapy. Univariate analysis revealed that the disease activity score 28-count erythrocyte sedimentation rate (ESR) at baseline (odds ratio [OR]: 4.298) was associated with progression of MDI. But multivariate logistic regression revealed that there was no association with the progression of MDI. Univariate analysis revealed that ESR at baseline (OR: 0.967) and matrix metalloproteinase-3 (MMP-3) at baseline (OR: 0.996) were associated with the progression of UMI. Multivariate logistic regression revealed that MMP-3 at baseline (OR: 0.994) was independently associated with the progression of UMI. Conclusion: Medial displacement index and UMI correlated with the Larsen grade of the shoulder joint strongly and moderately, respectively. This study suggests that MDI and UMI may help to evaluate radiographic progression of damage in shoulder joints in patients on bDMARDs, which is difficult to detect using the Larsen grade.